A Detailed Analysis of the Morphology of Fibrils of Selectively Mutated Amyloid β (1–40). Issue 17 (27th June 2016) - Adler, Juliane; Baumann, Monika; Voigt, Bruno; Scheidt, Holger A.; Bhowmik, Debanjan; Häupl, Tilmann; Abel, Bernd; Madhu, Perunthiruthy K.; Balbach, Jochen; Maiti, Sudipta; Huster, Daniel
Abstract: A small library of rationally designed amyloid β [Aβ(1–40)] peptide variants is generated, and the morphology of their fibrils is studied. In these molecules, the structurally important hydrophobic contact between phenylalanine 19 (F19) and leucine 34 (L34) is systematically mutated to introduce defined physical forces to act as specific internal constraints on amyloid formation. This Aβ(1–40) peptide library is used to study the fibril morphology of these variants by employing a comprehensive set of biophysical techniques including solution and solid‐state NMR spectroscopy, AFM, fluorescence correlation spectroscopy, and XRD. Overall, the findings demonstrate that the introduction of significant local physical perturbations of a crucial early folding contact of Aβ(1–40) only results in minor alterations of the fibrillar morphology. The thermodynamically stable structure of mature Aβ fibrils proves to be relatively robust against the introduction of significantly altered molecular interaction patterns due to point mutations. This underlines that amyloid fibril formation is a highly generic process in protein misfolding that results in the formation of the thermodynamically most stable cross‐β structure. Abstract : Robust fibrils : A library of rationally designed amyloid β peptide variants is generated and the morphology of their fibrils studied. This revealed that the structure of amyloid β fibrils is very robust against the introduction of defined physical forces that modify the structurally important hydrophobic contact between phenylalanine 19 and leucine 34 (see figure).